RETROSPECTIVE ANALYSIS OF MANDIBULAR FRACTURES CASES IN CENTER OF THE EASTERN ANATOLIA REGION OF TURKEY - Adnan Kılınç; Ümit Ertaş; Ertan Yalçın; Nesrin Saruhan (Cumhuriyet University, 2017)
Objectives: The aim of this retrospective study is to evaluate the etiology of mandibular fractures, the distribution of the age and gender of mandibular fracture patients, the anatomical regions where these fractures are located, and the treatment modalities used in mandibular fracture cases.Materials and Methods: This study employed data obtained via clinical records and the files of patients diagnosed with a mandibular fracture who were treated from 2011 to 2015 at the Department of Oral and Maxillofacial Surgery, Ataturk University.  The etiology of these patients' mandibular fractures, the distribution of these patients' age and gender, the anatomical regions where these patients' fractures were located, and the treatments applied to these patients were recorded by analyzing the obtained data.  Descriptive statistical analysis was performed using Microsoft Excel software.Results: 137 mandibular fracture sites were seen in 103 patients. Of these patients, 81 (79%) were male and 22 (21%) female, making the male-to-female ratio 3.7:1. The patients' ages ranged between 4 and 78 years, and the mean age was 31.4. Of the various etiologies of mandibular fractures, traffic accident (42 patients, 41%) was most frequent, followed by violence (28 patients, 27%), fall (24 patients, 23%). Of the various anatomical sites where mandibular fractures occurred, the condylar site (36 patients, 26%) was the most common, followed by the body (24%), symphysis and parasymphysis (23%), angle (18%). 58 patients (56%) were treated with closed reduction 42 patients (41%) were treated with open reduction. Three patients (3%) did not receive any treatment.Conclusions: Traffic accidents are the most common etiologic factor of mandibular fracture cases in center of the Eastern Anatolia Region of Turkey. Males and young individuals are the most affected. The condylar site is the most common anatomical site.  Both closed and open reduction methods are commonly used for the treatment of mandibular fractures.